Pengembangan Student Career Spin (SCS) sebagai Media Bimbingan Karir Siswa Sekolah Menengah Pertama - Akhmad Vikry; Arga Satrio Prabowo; Lenny Wahyuningsih (STIKes Ibnu Sina Ajibarang, 2025)
The study aims to develop Student Career Spin (SCS) media to facilitate students in career planning. The method used is Research and Development (R&D) with the development of the 4D Thiagarajan model. The results of the product feasibility test obtained an average value of 85.94%, which means it is very feasible to be implemented. Limited trials were conducted on 10 grade IX students at Al-Izzah Integrated Islamic Middle School, Serang City. The data results were analyzed using descriptive analysis techniques and the Wilcoxon Match Pairs Test. The results of the Wilcoxon Match Pairs Test obtained a significance value (asymp Sig) of 0.005, which means that the value is less than 0.05. So the hypothesis is accepted and it can be concluded that the development of Student Career Spin (SCS) media can improve the career planning of grade IX students at Al-Izzah Integrated Islamic Middle School, Serang City.